The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s1368980007217975
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anthropometry as a predictor of birth weight

Abstract: Objective: To determine whether maternal anthropometry predicted birth weight, and if so, to identify which cut-offs provided the best prediction of low birth weight (LBW) in a field situation. Design: Community-based longitudinal study. Setting: A rural union of Bhaluka Upazila, Mymensingh, located 110 km north-west of Dhaka, the capital of Bangladesh. Participants: A total of 1104 normotensive, non-smoking pregnant women who attended community nutrition centres were studied from first presentation at the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
4
32
0
3
Order By: Relevance
“…In contrast to these findings some studies 2, 3, 5, 6, 17 did not report significant relationships between neonatal Our data indicated that, of all the maternal measurements evaluated in this study, prepregnancy maternal weight was the strongest predictor of neonatal BW. This is in complete agreement with studies done in Bangladesh 18 and USA 4 . Based on the standardized regression coefficient, increase in the pre-pregnancy weight by 1 standard deviation, will increase by 0.222 standard deviations of neonatal BW.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to these findings some studies 2, 3, 5, 6, 17 did not report significant relationships between neonatal Our data indicated that, of all the maternal measurements evaluated in this study, prepregnancy maternal weight was the strongest predictor of neonatal BW. This is in complete agreement with studies done in Bangladesh 18 and USA 4 . Based on the standardized regression coefficient, increase in the pre-pregnancy weight by 1 standard deviation, will increase by 0.222 standard deviations of neonatal BW.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a birthweight greater than 4.0 kg is associated with an increased risk of obesity in both childhood and adolescence . This increased birthweight could be due in part to a decreased prevalence of smoking, and increases in maternal age, gestational diabetes , and maternal overweight and obesity .…”
mentioning
confidence: 99%
“…Status gizi Ibu sebelum hamil dapat ditentukan dengan indikator berat badan, tinggi badan, Indeks Massa Tubuh (IMT), dan Lingkar Lengan Atas (LiLA). Status gizi yang baik pada ibu sebelum hamil menggambarkan ketersediaan cadangan zat gizi dalam tubuh ibu yang siap untuk mendukung pertumbuhan janin pada awal kehamilan (Nahar 2007;Rosha et al 2012). Hasil penelitian di Kabupaten Magelang menunjukkan adanya hubungan yang signifikan antara paparan pestisida dengan kejadin BBLR (Setyobudi et al 2013) serta penelitian yang dilakukan di Soppeng menunjukkan adanya pengaruh faktor maternal terhadap kejadian BBLR (Rahmawati & Nur 2010).…”
Section: Pendahuluanunclassified